2012
DOI: 10.1016/j.nano.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing radiation increases systemic nanoparticle tumor accumulation

Abstract: Nanoparticle-based therapies are currently being explored for both the imaging and treatment of primary and metastatic cancers. Effective nanoparticle cancer therapy requires significant accumulations of nanoparticles within the tumor environment. Various techniques have been used to improve tumor nanoparticle uptake and biodistribution. Most notable of these techniques are the use of tumor-specific-peptide-conjugated nanoparticles and chemical modification of the nanoparticles with immune-evading polymers. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 7 publications
1
38
0
1
Order By: Relevance
“…Karathanasis et al effectively correlate tumor accumulation of iodinated liposomes to markers of blood vessel permeability (i.e., VEGF and VEGF receptor-2) [58], as well as therapeutic efficacy of doxorubicin-loaded liposomes in a separate report [15]. Other studies have demonstrated the impact of nanosystems, tumor properties, and modulating interventions on assessing the status and exploitation of the EPR effect at the whole-tumor level [14,[59][60][61]. Beyond the goal of achieving maximum tumor accumulation macroscopically -for which the direct impact on antitumor efficacy remains elusive -achievement of a favorable underlying micro-accumulation of nanomedicines may contribute significantly to an overall anti-tumor response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karathanasis et al effectively correlate tumor accumulation of iodinated liposomes to markers of blood vessel permeability (i.e., VEGF and VEGF receptor-2) [58], as well as therapeutic efficacy of doxorubicin-loaded liposomes in a separate report [15]. Other studies have demonstrated the impact of nanosystems, tumor properties, and modulating interventions on assessing the status and exploitation of the EPR effect at the whole-tumor level [14,[59][60][61]. Beyond the goal of achieving maximum tumor accumulation macroscopically -for which the direct impact on antitumor efficacy remains elusive -achievement of a favorable underlying micro-accumulation of nanomedicines may contribute significantly to an overall anti-tumor response.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing reports of the intratumoral distribution of small-molecule [1][2][3][4][5], macromolecular [6], and nanoparticle-based agents [7][8][9][10] have yielded insight into the impact of the physico-chemical properties of the drug delivery system as well as that of the tumor microenvironment [11] on anti-tumor efficacy. Specifically, the fate of nano-based agents at the tumor site has been examined in relation to select pathophysiological properties of tumors deemed critical to the success of nanomedicines such as the distribution of the tumor vascular network [11], vascular density [12,13] and permeability [14,15], as well as the composition and density of scaffold proteins of the extracellular matrix [16,17]. Such studies have significantly contributed to our understanding of the underlying barriers hindering the homogeneous distribution of nanomedicines within tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have demonstrated that modulating either the tumor microcirculation or IFP can influence the micro-regional and bulk accumulation of nanoparticles, including liposomes, in solid tumors [15][16][17][18][19][20]. Modulating the tumor microenvironment is often associated with changes to both tumor blood flow (TBF) and IFP, suggesting a coupling of these properties [13,21].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…To overcome these barriers, a single 15 Gy dose of radiation applied to a mouse mammary adenocarcinoma, decreased the interstitial pressure by 40% and increased vascular permeability at 3 days post-radiation compared with controls [32]. Furthermore, administration of iron oxide NPs following this procedure resulted in its twofold greater accumulation compared with unirradiated tumors.…”
Section: Radiation-mediated Enhancement Of Tumor Drug Deliverymentioning
confidence: 99%